Reading Amount and Reading Strategy as Mediators of the Effects of Intrinsic and Extrinsic Reading Motivation on Reading Achievement - Wang, Xiaocheng; Jia, Lina; Jin, Yuanying (Frontiers in Psychology, 2020)
This study was conducted to examine the roles of reading amount and reading strategy as mediators of the effects of intrinsic and extrinsic reading motivation on reading achievement. A sample of 522 7th–9th graders from two public schools in Eastern China participated in the study and completed the questionnaires. The confirmatory factor analyses showed that Curiosity, Involvement, and Challenge as dimensions of intrinsic reading motivation and Recognition, Grades, and Competition as dimensions of extrinsic reading motivation represented reading motivation well in this Chinese sample population. Structural equation modeling analyses showed that intrinsic reading motivation had a positive direct effect on reading achievement, whereas extrinsic reading motivation exerted a negative direct effect on reading achievement. Both intrinsic and extrinsic reading motivation positively predicted reading strategy; however, only intrinsic reading motivation was positively correlated with reading amount. Neither reading amount nor reading strategy mediated the effects of intrinsic and extrinsic reading motivation on reading achievement. The implications of these findings for literacy research and instruction are discussed.